A Patient with Non-Hodgkin Lymphoma and Nonspecific Interstitial Pneumonia during Ibrutinib Therapy - Sven Jungmann; Wolf-Dieter Ludwig; Nicolas Schönfeld; Torsten-Gerriet Blum; Claudia Großwendt; Christian Boch; Beate Rehbock; Sergej Griff; Alexander Schmittel; Torsten T. Bauer (Case Reports in Oncological Medicine, 2017)
We present a 74-year-old male with nonspecific interstitial pneumonia (NSIP) during treatment with ibrutinib for mantle cell lymphoma. Previously, the patient had received six cycles of bendamustine and rituximab and six cycles of R-CHOP, followed by rituximab maintenance therapy. Respiratory tract complications of ibrutinib other than infectious pneumonia have not been mentioned in larger trials, but individual case reports hinted to a possible association with the development of pneumonitis. In our patient, the onset of alveolitis that progressed towards NSIP together with the onset of ibrutinib treatment suggests causality. One week after ibrutinib was discontinued, nasal symptoms resolved first. A follow-up CT showed a reduction in the reticular hyperdensities and ground-glass opacities, suggestive of restitution of the lung disease. To our knowledge, this is the first case showing a strong link between ibrutinib and interstitial lung disease, strengthening a previous report on subacute pneumonitis. Our findings have clinical implications because pulmonary side effects were reversible at this early stage. We, therefore, suggest close monitoring for respiratory side effects in patients receiving ibrutinib.